The Role of Standard Operating Procedures in Elderly Posyandu Services at the Doi-Doi Community Health Center UPT in Mattappawalie Village, Pujananting District, Barru Regency - M, A.Pananrangi; Marsuki, Marsuki (Sean Institute, 2025)
This study aims to analyze the role of Standard Operating Procedures (SOPs) in improving the quality of services at the Elderly Integrated Health Post (Posyandu) at the Doi-Doi Community Health Center (Puskesmas) in Mattappawalie Village, Pujananting District, Barru Regency. SOPs are essential guidelines that standardize each stage of service delivery to ensure efficiency, effectiveness, and responsiveness to the needs of the elderly. This study employed a qualitative approach, collecting data through observation, in-depth interviews, and documentation. The results indicate that the existence of SOPs has a positive impact on the timeliness of services, clarity of staff workflows, and increased satisfaction among the elderly. However, challenges remain, such as a lack of understanding among some staff and suboptimal socialization and routine training. Therefore, SOPs play a crucial role not only as a technical reference but also as a tool for continuous service quality improvement at the Posyandu for the elderly. Capacity building of health workers and cadres is necessary through regular technical guidance to maximize SOP implementation.